2015
DOI: 10.1021/jacs.5b05289
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Brilliant Colors of the Sapphirinid Copepods

Abstract: Males of sapphirinid copepods use regularly alternating layers of hexagonal-shaped guanine crystals and cytoplasm to produce spectacular structural colors. In order to understand the mechanism by which the different colors are produced, we measured the reflectance of live individuals and then characterized the organization of the crystals and the cytoplasm layers in the same individuals using cryo-SEM. On the basis of these measurements, we calculated the expected reflectance spectra and found that they are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 28 publications
(6 reference statements)
4
107
0
Order By: Relevance
“…The copepods possess multilayer reflectors underneath their chitin cuticle. [54][55][56] Correlative cryo-SEM and reflectance measurements showed that the males have the remarkable ability to reversibly change their reflectance spectrum in response to changes in the light conditions. [54][55][56] Correlative cryo-SEM and reflectance measurements showed that the males have the remarkable ability to reversibly change their reflectance spectrum in response to changes in the light conditions.…”
Section: Tunable Reflectorsmentioning
confidence: 99%
“…The copepods possess multilayer reflectors underneath their chitin cuticle. [54][55][56] Correlative cryo-SEM and reflectance measurements showed that the males have the remarkable ability to reversibly change their reflectance spectrum in response to changes in the light conditions. [54][55][56] Correlative cryo-SEM and reflectance measurements showed that the males have the remarkable ability to reversibly change their reflectance spectrum in response to changes in the light conditions.…”
Section: Tunable Reflectorsmentioning
confidence: 99%
“…The aragonite platelets are typically stacked and arrangements within the organic matrix ('columnar nacre') were reported as well as a 'brick-and-mortar'-like structure ('sheet nacre') [4]. Besides the superior mechanical performance, some biomaterials also display additional functionality that includes, for example, outstanding optical [13][14][15][16] or magnetic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, theoretical and experimental interest in guanine multilayer reflectors was very high because of potential biomimetic applications (Bossard et al, 2016;Iwasaka et al, 2016;Hirsch et al, 2015;del Barco et al, 2015;Gur et al, 2015aGur et al, ,b, 2013 . Raman spectra of pigments from dark blue skin melanophores of panther chameleons (Teyssier et al, 2015) and red skin erythrophores of the lizard Phelsuma lineata (Saenko et al, 2013) exhibit two similar peaks, but the region around 1600 cm −1 is different.…”
Section: Tapetum Structurementioning
confidence: 99%